Literature review for the analysis of the performance of the SWAT model in Future Water Availability (Aporte Santiaguino, 2024)
Climate change is a global problem that is affecting the availability of surface water worldwide. Extreme weather events are increasing according to future predictions, this causes changes in precipitation patterns, intensifying droughts and floods. The objective of the research was to carry out a systematic review of articles indexed from 2014 to 2024, referring to the performance of the SWAT model in future water availability. The materials and methods were based on two well-marked stages; the literature search and literature review, the first stage corresponds to the identification of the literature in the Scopus database, applying a search string in articles published in the last 10 years, and then performing a filter applying 2 selection criteria and finally the second stage, which integrates the information by ordering it and extracting the most relevant for the analysis. The review and analysis carried out showed good performance in most of the studies that used the SWAT model in the simulations; For the most part, there is a trend toward decreased rainfall and water availability. In conclusion, the SWAT model performed well in most of the studies reviewed; In most future projections there is a trend towards a decrease in rainfall and water availability.
Keywords: Climate change; Water availability; SWAT; Systemic review